Application of nanotechnological delivery systems in pancreatic cancer therapy - Fonseca, Leonor Castro da (2020)
The aim of this dissertation is to understand the applications of nanotechnology in the delivery of drugs in pancreatic cancer therapy. It was necessary to realize the pathogenesis of pancreatic cancer, as well as the reasons why conventional therapies currently used do not provide a significant increase in patient survival. Pancreatic cancer is one of the most lethal cancers in the world, mainly because of the inability to diagnose it in a timely manner and the lack of effectiveness of existing treatments. In this way, the development of new innovative therapies has become fundamental. In the last decade, nanomedicine has gained increasing prominence as a new approach for the delivery of drugs, since it allows the transport of the drugs to the specific region and in established concentrations, reducing in this way the systemic toxicity. Several studies are related to different types of nanoparticles (lipid, polymer and metal), highlighting the advantages and disadvantages of each of them, as well as some drugs already marketed using nanotechnology. A model administration system was developed for the delivery of Parvifloron D. The characteristics selected were related to the properties of the drug to be encapsulated, with diameters of 200nm, negative zeta potential, IdP of 0.200 and connection efficiency of 97%. The toxicity of the formulation was also evaluated, and it was concluded that the lower concentration nanoparticles (30 μM) provided a growth inhibition of 3.2% Saccharomyces cerevisiae, and at the highest concentration (53 μM) of 15.6%. These results lead us to believe that through further studies it may be possible to use this optimized formulation as a suitable and promising carrier of Parvifloron D, and thus contribute to a therapeutic alternative for pancreatic cancer.